The perspective of children of migrant workers (TKI) on physical and emotional changes during puberty: A study at CLC Ladong Simunjan, Kuching, Sarawak - Kaissa Melian; Eva Imania Eliasa (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2025)
Puberty is an important stage in a child's development marked by significant physical and emotional changes. Children at the Ladang Ladong Community Learning Center (CLC), Simunjan, face this phase amidst limited information and support. This research aims to explore children's perspectives at CLC Ladang Ladong regarding their experiences during puberty, especially regarding physical and emotional changes. Using a qualitative approach and in-depth interview methods, data was collected from several puberty-aged children who attended CLC. The results showed that children have varying understandings about changes in their bodies and emotions. Some of them felt confused and lacked self-confidence, while others showed good adaptation. Factors such as communication with parents, the role of teachers, and the social environment contribute to how they deal with these changes. This research underlines the importance of holistic education and better emotional support from the surrounding environment in helping children face puberty.